2018
DOI: 10.1128/iai.00429-18
|View full text |Cite
|
Sign up to set email alerts
|

Methylthioadenosine Suppresses Salmonella Virulence

Abstract: In order to deploy virulence factors at appropriate times and locations, microbes must rapidly sense and respond to various metabolite signals. Previously, we showed a transient elevation of the methionine-derived metabolite methylthioadenosine (MTA) concentration in serum during systemic Salmonella enterica serovar Typhimurium infection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 79 publications
0
18
4
1
Order By: Relevance
“…As a consequence of its pervasive presence, MTA regulates, directly or indirectly, expression, activity or both, of enzymes involved in methionine, AdoMet or polyamine biosynthesis (Anashkin et al, 2017). Being similar to AdoMet, but smaller, MTA often interferes with AdoMet synthesis or other processes (see for example Pang et al, 2017), with a variety of consequences on methionine availability, including inhibition of virulence of pathogens and production of antibiotics (Tojo et al, 2014;Wang et al, 2017;Bourgeois et al, 2018). The outcome of this constraint is that the level of the molecule is generally kept low in cells.…”
Section: Blue Arrows)mentioning
confidence: 99%
“…As a consequence of its pervasive presence, MTA regulates, directly or indirectly, expression, activity or both, of enzymes involved in methionine, AdoMet or polyamine biosynthesis (Anashkin et al, 2017). Being similar to AdoMet, but smaller, MTA often interferes with AdoMet synthesis or other processes (see for example Pang et al, 2017), with a variety of consequences on methionine availability, including inhibition of virulence of pathogens and production of antibiotics (Tojo et al, 2014;Wang et al, 2017;Bourgeois et al, 2018). The outcome of this constraint is that the level of the molecule is generally kept low in cells.…”
Section: Blue Arrows)mentioning
confidence: 99%
“…It is well established that B cells are targets of Salmonella infection . In murine models, we observed that Salmonella Typhimurium is able to infect and survive within spleen B cells for up to 60 d postinfection .…”
Section: Bacteria Capable Of Infecting B Cellsmentioning
confidence: 79%
“…It is well established that B cells are targets of Salmonella infection. [22][23][24][25][26][27][28] In murine models, we observed that Salmonella…”
Section: Spi-5 Encodes a Series Of Proteins Responsible For Enteropatmentioning
confidence: 99%
“…Nevertheless, experimental evidence has demonstrated that it is possible to inhibit MTA/SAH nucleosidase activity without severely affecting bacterial growth and without inducing resistance toward inhibitors (Gutierrez et al, 2009). In addition, Bourgeois et al (2018) observed that a Salmonella enterica serovar Typhimurium Δ metJ mutant strain, which was defective in methionine metabolism, presented elevated intracellular MTA levels without affecting bacterial growth (Bourgeois et al, 2018). In a S. aureus pfs mutant strain ( pfs encodes the MTA/SAH nucleosidase), growth was not impaired in nutrient-rich conditions but it was affected in zebrafish embryos (Bao et al, 2013).…”
Section: Methylthioadenosine/s-adenosylhomocysteine Nucleosidase Inhimentioning
confidence: 99%